The Reality of Audit Practices at the Libyan Audit Bureau and the Extent of Their Compliance with the International Standards on Auditing (ISA) (200, 220) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to analyse the reality of audit practices within the Libyan Audit Bureau and to assess their compliance with the requirements of the International Standards on Auditing (ISA200), (ISA220), given their pivotal role in defining professional responsibilities and ensuring quality performance in audit engagements. The significance of the study stems from the need to evaluate the extent to which regulatory bodies in Libya adhere to international standards, thereby enhancing the reliability of government financial reports and improving the efficiency of audit performance. The research problem lies in the potential gap between the formal adoption of international standards and their actual implementation within the Bureau, particularly in light of the institutional and environmental challenges facing audit work in Libya. The study employed a descriptive-analytical approach and relied on a field survey involving 119 auditors from the Bureau’s technical departments. The questionnaire consisted of (36) items distributed across four main dimensions representing the scope of analysis: ethical dimension, risk dimension, technical dimension, and supervision and quality dimension. Data were analysed using factor analysis, which revealed six principal dimensions of (ISA200), (ISA220), explaining (64.205%), of the total variance. The behavioural/ethical and technical dimensions separated into independent factors, namely professional judgment, evidence, independence, and ethics. Meanwhile, items from different dimensions converged into a single practical factor representing the implementation stage (audit execution, results analysis, and response to deficiencies). The supervision and quality dimension split into two main factors: team quality and administrative oversight on one hand, and independent review and compliance monitoring on the other. This distinction reflects respondents’ differentiation between internal and external supervision. The most prominent factor was leadership, planning, and responsibility for engagement quality, followed by ethical commitment and performance monitoring, indicating a high level of professional alignment with the requirements of the two standards. The findings also revealed a limited gap in the dimensions of independence and supervision, highlighting the need to strengthen institutional control mechanisms and professional development. The study concludes that the Libyan Audit Bureau conducts audits with a high degree of professional discipline, while emphasizing the necessity of reinforcing auditor independence and activating peer review to ensure audit quality in the future.
Keywords: Libyan Audit Bureau; International Standards on Auditing (ISA 200); (ISA 220); Audit Quality; Professional Judgment and Independence; Professional Ethics; Supervision and Quality